(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background: Hordeum distichon L. is the most important cereal crop grown in Iraq and is commonly cultivated in temperate climate across the world that is often known as common barley or two-rowed barley is a cultigen of barley belonging to the Poaceae family and the Triticeae tribe. Results: The present review summarized collected information that is spread in different scientific articles about Hordeum distichon’s morphology, ethnomedicinal uses, phytochemistry, and pharmacology. It was also gathered scientific evidence supporting ethnobotanical claims and identified holes that must be filled by future study Conclusion: These data will be helpful to provide future directions for the agricultural and medicinal use of Hordeum distichon plant which no need to remain the most extensively used herbal plant, according to traditional applications and scientific examination.